Ciclos biogeoquímicos en un ecosistema forestal de los Andes Occidentales de Venezuela, 3: Ciclo hidrológico y translocación de elementos químicos con el agua [suelos]. - Grimm, U; Fassbender, H.W. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The annual hydrological budget in the montane forest ecosystem of San Eusebio, Mdrida, Venezuela, was studied and water samples collected and analysed for chemical composition. Total rainfall was 1 576 mm, canopy rainfall 1 260 and stem flow 12 mm. The soil water content of the soil and its changes were calculated based on tensiometer readings and pF-curve. An evapotranspiration of 980 nun was calculated from meteorological data. Percolating water was collected with ceramic lysimeters and calculated from above data to be 588 mm. In order to calculate the chemical transfer of elements, 192 water samples were analysed for pH, N, P, K, Ca, Mg, Mn, Fe and Al. The chemical input into the ecosystem depends primarily on the rainfall paterns in the region. The high values for N and Na are related to marine aerosols, gases from petrochemical industries and soil particles. The concentration in the percolating waters are lower than the rainfall, so that there is a chemical accumulation in the ecosystems.